‘‘I can’t stop worrying about everything’’-experiences of rural Bangladeshi women during the first postpartum months - Edhborg, Maigun; Nasreen, Hashima E; Kabir, Zarina Nahar (Co-Action Publishing, 2015)
Over recent years, researchers have found evidence which indicates that the prevalence of postpartum depressive symptoms crosses cultural boundaries and is reported to be at least as high in non-Western countries as inWestern countries. However, qualitative studies about new mothers’ experiences from non-Western countries, such as Bangladesh, are rare, particularly in rural areas. This study aims to describe the experiences and concerns of rural Bangladeshi mothers with postpartum depressive symptoms. Open narrative interviews were conducted with 21 mothers with depressive symptoms 2-3 months postpartum, consecutively selected from a longitudinal study about prevalence and risk factors of perinatal depressive symptoms. Inductive content analysis was used to analyse data and three themes emerged: family dynamics, living at the limits of survival, and role of the cultural context after childbirth. These themes were based on six categories and 15 subcategories. The findings show that troublesome family relationships, including intimate partner violence and violence in the family, influenced the mothers’ mental well-being. They and their families lived at the limit of survival and the mothers expressed fear and worries about their insecure situation regarding economic difficulties and health problems. They felt sorry for being unable to give their infants a good start in life and sad because they could not always follow the traditional norms related to childbirth. Thus, it is important to focus on the depressive symptoms among new mothers and offer counselling to those showing depressive symptoms, as the cultural traditions do not always alleviate these symptoms in the changing Bangladeshi society today.